Countable compactness with respect to ideal via β-open sets (Journal of Pure and Applied Sciences (Science Forum), 2026)
In this paper, we study countable β-compactness and present another new class of compactness in ideal topological space via countable βρI-compact spaces by utilizing the notion of β-open sets. We also properties investigate some other of countable βρI-compactness using different types of functions.